Chemoprotective Effect of Eugenol against Single Dose Doxorubicin (DOX)-Induced Toxicopathological Alterations in Swiss Albino Mice with Special Reference to Cardiotoxicity - Nitin Jadhav, Mayuri; Arvind Chandratre, Gauri; Lather, Deepika; Bagri, Preeti; Nehra, Vikas (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Doxorubicin (DOX), is utilized in the treatment of various canine and feline cancers. However, its therapeutic application is associated with marked adverse effects on heart as well as myelosuppression and potential for secondary malignancy. In order to reduce the side effects, potential of eugenol was investigated against Doxorubicin in Swiss albino mice. Toxicity was induced by a single intraperitoneal injection of doxorubicin (25 mg/kg, b.wt.) and Eugenol treatment (10 mg/kg/day, orally) was initiated 15 days before doxorubicin administration. Oral administration of eugenol markedly alleviated DOX-induced oxidative stress in cardiac tissues, as evidenced by reduced levels of lipid peroxidation, nitric oxide. Furthermore, eugenol enhanced the activity of antioxidant enzymes, including catalase and superoxide dismutase. In addition to attenuating oxidative stress, eugenol administration significantly reduced DOX-induced inflammation by downregulating the gene expression of pro-inflammatory mediators, namely, TNF alpha, iNOS and IL. Gross and histopathological examinations revealed substantial structural and functional impairment in the heart, brain, liver, spleen, bone marrow and kidney due to DOX intoxication. This study suggests the promising chemoprotective efficacy of eugenol against DOX-induced toxicopathological alterations, indicating its potential as an adjuvant in chemotherapy.